2017
DOI: 10.1016/j.compscitech.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Electrically and thermally conductive thin elastic polymer foils containing SiC nanofibers

Abstract: Design and experiment of polymeric nanocomposites (NCs) for photovoltaic applications with outstanding electrical and thermal properties has been investigated with the introduction of SiC nanofibers (NFs) into the poly(trimethylene terephthalate)-blockpoly(tetramethylene oxide) (PTT-PTMO) copolymers. In order to enhance the electrical and thermal conductivity, different concentrations of SiC NFs, ranging from 0.1 to 3.0 wt %, have 2 been selected to mix with PTT-PTMO via in situ polymerization method. This rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
(42 reference statements)
3
8
0
Order By: Relevance
“…Moreover, as shown in Figure 4, for nanocomposites with SiC nanofibers, the values of electrical conductivity in low frequency range exhibit higher values than those of pristine matrix. This fact suggests that there are many connections between nanofibers, with small gaps of polymer between them, which promotes polarization phenomena [26]. Our further study on the electrical properties of PTT-PTMO/SiC nanocomposites with higher content of SiC confirmed the electrical percolation threshold (φ c ) equals to 1.7 [26].…”
Section: Elastomerssupporting
confidence: 56%
See 3 more Smart Citations
“…Moreover, as shown in Figure 4, for nanocomposites with SiC nanofibers, the values of electrical conductivity in low frequency range exhibit higher values than those of pristine matrix. This fact suggests that there are many connections between nanofibers, with small gaps of polymer between them, which promotes polarization phenomena [26]. Our further study on the electrical properties of PTT-PTMO/SiC nanocomposites with higher content of SiC confirmed the electrical percolation threshold (φ c ) equals to 1.7 [26].…”
Section: Elastomerssupporting
confidence: 56%
“…Thus, the SEM Elastomers images of NCs surface suggest the "pulling out" SiC NFs from the polymer matrix during the brittle fracture of the sample [10]. Thus, it can be concluded that 1D type nanofillers, that is, SWCNTs, SiC NFs, with high aspect ratio distinctly represent their efficiency for avoiding the existence of agglomerates due to the high shear mixing with high-frequency vibration [10][11][12]26], thus confirming the legitimacy of the use of in situ method to obtain nanocomposites.…”
Section: Nanocomposite Morphologiesmentioning
confidence: 94%
See 2 more Smart Citations
“…This material exhibits excellent thermoplastic elastomer properties, such as a low glass transition temperature, high melting point, and a temperature-independent rubbery plateau [28]. However, more recently, it was found that the properties of PTT-PTMO can be further improved by the addition of either inorganic particles like montmorillonite (MMT) [29], POSS [23], silicon carbide nanofibers (SiC) [30] or organic nanofillers such as single-walled carbon nanotubes (SWCNT) [31], graphene oxide [32] or even a hybrid system of nanofillers like SWCNT and graphene nanoplatelets (GNP) [33,34]. However, it was found that at the same concentration, carbon nanofillers (like SWCNT or GNP) affect the polymer matrix in stronger manner [35].…”
Section: Introductionmentioning
confidence: 99%